A highly stable indium phosphonocarboxylate framework as a multifunctional sensor for Cu2+ and methylviologen ions. Issue 8 (22nd January 2015) - Dan, Wenyan; Liu, Xiaofeng; Deng, Mingli; Ling, Yun; Chen, Zhenxia; Zhou, Yaming
Abstract : An indium phosphonocarboxylate framework (InPCF-1 ) with a novel 3, 4, 5-connected topology was synthesized, which serves as a selective and sensitive sensor for Cu 2+ and MV 2+ ions. Abstract : An indium phosphonocarboxylate framework, H3 O[In(pbpdc)]·3H2 O n (InPCF-1 ) (pbpdc = 4′-phosphonobiphenyl-3, 5-dicarboxylate), was hydrothermally synthesized. The structure ofInPCF-1 features the inorganic chains as rod-shaped second building units. The rod-packing arrangement results in a three-dimensional (3-D) framework with a novel (3, 4, 5)-connected net. Studies of the gas adsorption, and thermal and chemical stability ofInPCF-1 demonstrated its adsorption capacity for CO2, selective separation of CO2 over O2 and N2, high thermal stability, and a remarkable chemical resistance to boiling water, ethyl alcohol, and methylbenzene. Importantly, InPCF-1 shows a selective and sensitive response to Cu 2+ ions. It also serves as a sensor for methylviologen.